Alkali-resistant hydrolysis polyimide engineering plastic and preparation method thereof

By mixing the hyperplastic polyamine solution and modified polyamide solution, it is made of dehydration reactions to make alkaline resistance hydrolytic polytamide engineering plastics, which solves the problem of polyperamine impact and hydrolysis, which significantly improves Its mechanical properties and alkali resistance.

CN119371821AActive Publication Date: 2025-01-28GUANGDONG HUANSU ZHONGCHUANG IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411388147.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-28
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Existing polyimides are not resistant to alkaline hydrolysis, and have weak mechanical strength and toughness.

Method used

By mixing the hyperplastic polyamine solution and the modified polyamide solution, it is made of dehydration reactions to make alkaline -resistant hydrolytic polytamide engineering plastics. This method uses the spatial position effect of the overflow polyamide and the enhancement effect of the filling of nanoparticles to improve the mechanical properties and stability of polytide.

Benefits of technology

It significantly improves the mechanical properties and alkali resistance of polytide, and enhances its stability and ultraviolet light performance under alkaline conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to alkali-resistant hydrolysis polyimide engineering plastic and a preparation method thereof, and belongs to the technical field of polyimide engineering plastic preparation. The hyperbranched polyamic acid is prepared by mixing a hyperbranched polyamic acid solution, a modified polyamic acid solution and a dehydrating agent and then carrying out a dehydration reaction, the hyperbranched polyamide acid solution is prepared by carrying out in-situ polymerization reaction on modified nanoparticles, a first dianhydride monomer and a ternary amine monomer in a first solvent; the modified polyamide acid solution is prepared by carrying out polymerization reaction on a second dianhydride monomer and a branched chain-containing diamine monomer in a second solvent; the branched chain-containing diamine monomer is prepared by reacting aniline and a benzaldehyde derivative; the benzaldehyde derivative is prepared from 4-hydroxybenzaldehyde and an epoxy silane coupling agent through a reaction. The polyimide engineering plastic contains hyperbranched polyimide and chain polyimide, has good mechanical strength and ultraviolet light resistance, and is stable under alkaline conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of polyimide engineering plastics, and in particular relates to an alkali-hydrolysis-resistant polyimide engineering plastic and a preparation method thereof. Background Art

[0002] Polyimide (abbreviated as PI) refers to a type of polymer containing an imide ring (-CO-NR-CO-) on the main chain. It is one of the organic polymer materials with the best comprehensive performance. It has excellent temperature resistance (high temperature can reach above 400°C, and the long-term practical temperature range can also reach -200~300°C), and has excellent electrical insulation performance. The dielectric constant is 4.0 at 103 Hz, and the dielectric loss is only 0.004~0.007, which belongs to F to H grade insulation. Due to the above excellent temperature resistance and electrical insulation performance, it has been widely used as a special engineering material in aviation, aerospace, microelectronics, nano, liquid crystal, separation membrane, laser and other fields.

[0003] However, polyimide is not resistant to alkaline hydrolysis. In view of the above-mentioned disadvantage of polyimide being not resistant to alkaline hydrolysis, there is an urgent need for an alkaline hydrolysis-resistant polyimide engineering plastic and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide an alkali-hydrolysis-resistant polyimide engineering plastic and a preparation method thereof.

[0005] The technical problem to be solved by the present invention is that the existing polyimide has the disadvantages of weak mechanical strength and toughness.

[0006] One object of the present invention can be achieved by the following technical solutions: An alkaline hydrolysis-resistant polyimide engineering plastic is prepared by mixing a hyperbranched polyamic acid solution, a modified polyamic acid solution and a dehydrating agent and then subjecting the mixture to a dehydration reaction; The hyperbranched polyamic acid solution is prepared by in-situ polymerization of modified nanoparticles, a first dianhydride monomer and a triamine monomer in a first solvent; The modified polyamic acid solution is prepared by polymerization reaction of a second dianhydride monomer and a branched diamine monomer in a second solvent; The branched diamine monomer is prepared by reacting aniline and benzaldehyde derivatives; The benzaldehyde derivative is prepared by reacting 4-hydroxybenzaldehyde and an epoxy silane coupling agent.

[0007] In the present invention, a hyperbranched polyamic acid solution and a chain-type polyamic acid solution are blended and then subjected to imidization treatment (i.e., dehydration operation) to obtain polyimide; Among them, the spatial position effect of hyperbranched polyamide is utilized to greatly reduce the interaction between the molecular chains of the chain-type polyimide, so that the organic solvent solubility of the polyimide obtained by imidization is improved, and the application and processability of the final polyimide are improved.

[0008] Furthermore, the modified nanoparticles are nanoparticles modified by a silane coupling agent, and the nanoparticles are nano-titanium dioxide or nano-zinc oxide; Here, the present invention utilizes the spatial loading characteristics of hyperbranched polyamide, and obtains a hyperbranched polyamide acid liquid with enhanced ultraviolet light resistance through the form of nano titanium dioxide modified by a silane coupling agent or nano zinc oxide modified by a silane coupling agent and an in-situ polymerization technology. First, the in-situ polymerization technology is utilized to improve the stability of the functional enhancement, and second, the nano titanium dioxide or zinc oxide is used to enable the hyperbranched polyamide acid liquid to obtain the intrinsic function of ultraviolet light resistance.

[0009] The nanoparticles modified with silane coupling agents are the surface modification techniques of nanoparticles with silane coupling agents well known in the art, and the present invention does not specifically limit them.

[0010] Further, the silane coupling agent is one of KH550, KH560, KH570, A151, A171, and A172; Preferably, the silane coupling agent is KH550.

[0011] Furthermore, the mass ratio of the hyperbranched polyamic acid solution to the modified polyamic acid solution is 1:1-3.

[0012] Furthermore, the solid content of the hyperbranched polyamic acid solution is 15-30wt%.

[0013] Preferably, the solid content of the hyperbranched polyamic acid solution is 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt% or 25wt%.

[0014] Furthermore, the solid content of the modified polyamic acid solution is 25-40wt%.

[0015] Preferably, the solid content of the modified polyamic acid solution is 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt% or 35wt%.

[0016] Furthermore, in the dehydration reaction, the dehydration reaction temperature is 70-130° C., and the reaction time is 5-12 h.

[0017] Furthermore, the molar ratio of the first dianhydride monomer to the triamine monomer is 3.5-4:2.

[0018] Preferably, the molar ratio of the first dianhydride monomer to the triamine monomer is 3.5:2, 3.6:2, 3.7:2, 3.8:2, 3.9:2 or 4:2.

[0019] Furthermore, in the in-situ polymerization reaction, the reaction temperature is 0-40° C. and the reaction time is 4-8 h.

[0020] Furthermore, the modified nanoparticles account for 15-35% of the total mass of the first dianhydride monomer and the triamine monomer.

[0021] Preferably, the modified nanoparticles account for 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35% of the total mass of the first dianhydride monomer and the triamine monomer.

[0022] Furthermore, the first dianhydride monomer is one of 4,4′-phthalic anhydride, 3,3′,4,4′-benzophenonetetracarboxylic dianhydride, pyromellitic dianhydride, and 4,4′-oxydiphthalic anhydride.

[0023] Furthermore, the triamine monomer is 4,4',4''-triaminotriphenylmethane.

[0024] Furthermore, the first solvent is one or more of N,N-methylformamide, N,N-methylacetamide, and N-methylpyrrolidone.

[0025] Furthermore, the molar ratio of the second dianhydride monomer to the branched diamine monomer is 1:1.

[0026] Furthermore, in the polymerization reaction, the reaction temperature is 0-40°C and the reaction time is 4-8h.

[0027] Furthermore, the second dianhydride monomer is one of 4,4′-phthalic anhydride, 3,3′,4,4′-benzophenonetetracarboxylic dianhydride, pyromellitic dianhydride, and 4,4′-oxydiphthalic anhydride.

[0028] Furthermore, the second solvent is one or more of N,N-methylformamide, N,N-methylacetamide, and N-methylpyrrolidone.

[0029] Furthermore, the branched diamine monomer is prepared by reacting aniline and benzaldehyde derivatives, comprising: After benzaldehyde derivative, aniline, aniline hydrochloride and dimethyl sulfoxide are uniformly mixed, reacted at 100-110°C under nitrogen protection for 1-3h, heated to 130-145°C, kept warm for 2-3h, cooled to stop the reaction, poured into water, flocculated and precipitated at low temperature, filtered to obtain the precipitate, dissolved the precipitate with hydrochloric acid, filtered to obtain the filtrate, neutralized the filtrate with sodium hydroxide to produce a precipitate, washed the precipitate repeatedly, and dried to obtain a branched diamine monomer.

[0030] Furthermore, the molar ratio of the benzaldehyde derivative to aniline is 1:2.5-3.

[0031] Furthermore, the added mass of the aniline hydrochloride is 3-6% of the mass of the benzaldehyde derivative and aniline.

[0032] In the above reaction, the aldehyde group in the benzaldehyde derivative and the hydrogen on the 4-carbon of aniline undergo a coupling dehydration reaction, that is, 1 mole of the benzaldehyde derivative reacts with 2 moles of aniline to generate a branched diamine monomer, and the branch is a siloxane chain. The main chain of the polyamide generated by the reaction of the branched diamine monomer and the second dianhydride monomer is connected to the siloxane chain, thereby improving the stability of the obtained polyimide under alkaline conditions.

[0033] The following is the chemical structure of the branched diamine monomer of epoxy silane coupling agent KH560: .

[0034] Furthermore, the benzaldehyde derivative is prepared by reacting 4-hydroxybenzaldehyde with an epoxy silane coupling agent, comprising: After 4-hydroxybenzaldehyde, epoxysilane coupling agent and tetrahydrofuran are uniformly mixed, the pH of the system is adjusted to 10-11, heated to reflux under condensation, stirred and reacted for 2-4 hours, cooled to 30-40°C, rotary evaporated, washed and dried to obtain a benzaldehyde derivative.

[0035] Furthermore, the molar ratio of the 4-hydroxybenzaldehyde to the epoxy silane coupling agent is 1:1-1.3.

[0036] The above reaction utilizes the reaction between the hydroxyl group in 4-hydroxybenzaldehyde and the epoxy group in the epoxysilane coupling agent, so that the siloxane chain is connected to the 4-position of the benzaldehyde.

[0037] Another object of the present invention can be achieved by the following technical solutions: A method for preparing an alkali-hydrolysis-resistant polyimide engineering plastic comprises: The hyperbranched polyamic acid solution, the modified polyamic acid solution and the dehydrating agent are mixed, heated to the dehydration reaction temperature, and kept warm for dehydration. After the dehydration is completed, the mixture is cooled, water or ethanol is added, stirred to precipitate, filtered, the precipitate is taken, and dried to obtain an impact-resistant high-toughness polyimide.

[0038] Furthermore, the amount of the dehydrating agent added is 3-5 times the total molar mass of the amino monomers provided in the hyperbranched polyamic acid solution and the modified polyamic acid solution, wherein the amino monomers provided are triamine monomers and branched diamine monomers.

[0039] Beneficial effects of the present invention: The invention adopts a method of blending a hyperbranched polyamic acid solution and a chain-type polyamic acid solution, and then performs imidization treatment to obtain a polyimide engineering plastic containing a hyperbranched polyimide and a chain-type polyimide. On the one hand, nanoparticles loaded with the hyperbranched polyimide are used to achieve a filling and reinforcing effect of the nanoparticles, thereby improving the mechanical properties of the polyimide engineering plastic finally obtained. On the other hand, the hyperbranched structure of the hyperbranched polyimide and the siloxane side chains in the chain-type polyimide synergistically improve the interpenetrating network of the obtained polyimide-polyimide engineering plastic, thereby further improving the mechanical properties. In addition, the obtained polyimide engineering plastic is stable under alkaline conditions and has good ultraviolet light resistance. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0041] Preparation of branched diamine monomers: A1. Evenly mix 0.1 mol 4-hydroxybenzaldehyde, 0.1 mol epoxysilane coupling agent (KH560) and 100 mL tetrahydrofuran, adjust the pH of the system to 10-11, heat to reflux under condensation, stir and react for 2 h, cool to 30-40 °C, rotary evaporate, wash and dry to obtain a benzaldehyde derivative.

[0042] A2. After uniformly mixing 0.1 mol of benzaldehyde derivative, 0.25 mol of aniline, aniline hydrochloride and 150 mL of dimethyl sulfoxide, react under nitrogen protection at 100°C for 3 h, heat the reaction to 130°C, keep the temperature for 3 h, cool down to stop the reaction, pour in water, flocculate and precipitate at low temperature, filter out the precipitate, dissolve the precipitate with hydrochloric acid, filter out the filtrate, neutralize the filtrate with sodium hydroxide to produce a precipitate, wash the precipitate repeatedly, and dry to obtain a branched diamine monomer; wherein the added mass of the aniline hydrochloride is 5% of the mass of the benzaldehyde derivative and aniline. Example

[0043] Preparation of branched diamine monomers: A1. Evenly mix 0.1 mol 4-hydroxybenzaldehyde, 0.13 mol epoxysilane coupling agent (KH560) and 100 mL tetrahydrofuran, adjust the pH of the system to 10-11, heat to reflux under condensation, stir and react for 4 h, cool to 30-40 °C, rotary evaporate, wash and dry to obtain a benzaldehyde derivative.

[0044] A2. After uniformly mixing 0.1 mol of benzaldehyde derivative, 0.3 mol of aniline, aniline hydrochloride and 150 mL of dimethyl sulfoxide, react under nitrogen protection at 110°C for 1 h, heat to 145°C, keep warm for 2 h, cool to stop the reaction, pour in water, flocculate and precipitate at low temperature, filter to obtain the precipitate, dissolve the precipitate with hydrochloric acid, filter to obtain the filtrate, neutralize the filtrate with sodium hydroxide to produce a precipitate, wash the precipitate repeatedly, and dry to obtain a branched diamine monomer; wherein the added mass of the aniline hydrochloride is 4% of the mass of the benzaldehyde derivative and aniline. Example

[0045] Preparation of polyimide engineering plastics: The first step is to prepare a hyperbranched polyamic acid solution: KH550-modified nano-titanium dioxide, 0.35 mol 4,4′-phthalic anhydride, 0.2 mol 4,4′,4′′-triaminotriphenylmethane and N,N-methylformamide are uniformly mixed to prepare a solution with a solid content of 15 wt%, and then reacted at 0°C under nitrogen protection for 8 hours to obtain a hyperbranched polyamic acid solution, wherein the modified nano-titanium dioxide accounts for 20% of the total mass of the 4,4′-phthalic anhydride and 4,4′,4′′-triaminotriphenylmethane, the particle size of the nano-titanium dioxide is 200-400 nm, and KH550 accounts for 6% of the mass of the nano-titanium dioxide in the KH550-modified nano-titanium dioxide.

[0046] Step 2: Preparation of modified polyamic acid solution: 0.1 mol of 4,4′-phthalic anhydride, 0.1 mol of the branched diamine monomer prepared in Example 1 and N,N-methylformamide were uniformly mixed to prepare a solution with a solid content of 25 wt%, and then reacted at 0° C. under nitrogen protection for 8 h to obtain modified polyamic acid solution.

[0047] Step 3, preparation of engineering plastics: after mixing the hyperbranched polyamic acid solution obtained in the first step and the modified polyamic acid solution obtained in the second step in a mass ratio of 1:2, add 1 mol of acetic anhydride, stir and heat to 70°C, and keep warm for dehydration for 12 hours. After dehydration, cool, add water or ethanol, stir to precipitate, filter, take the precipitate, and dry to obtain impact-resistant and high-toughness polyimide. Example

[0048] Preparation of polyimide engineering plastics: The first step is to prepare a hyperbranched polyamic acid solution: KH550-modified nano zinc oxide, 0.36 mol 3,3′,4,4′-benzophenone tetracarboxylic dianhydride, 0.2 mol 4,4′,4′′-triaminotriphenylmethane and N,N-methylacetamide are uniformly mixed to prepare a solution with a solid content of 20 wt%, and then reacted at 20° C. under nitrogen protection for 6 hours to obtain a hyperbranched polyamic acid, wherein the modified nano zinc oxide accounts for 25% of the total mass of the 3,3′,4,4′-benzophenone tetracarboxylic dianhydride and 4,4′,4′′-triaminotriphenylmethane, the particle size of the nano zinc oxide is 200-400 nm, and KH550 accounts for 9% of the mass of the nano zinc oxide in the KH550-modified nano zinc oxide.

[0049] Step 2: Preparation of modified polyamic acid solution: 0.1 mol of 3,3′,4,4′-benzophenonetetracarboxylic dianhydride, 0.1 mol of the branched diamine monomer prepared in Example 2 and N,N-methylacetamide were uniformly mixed to prepare a solution with a solid content of 30 wt%, and then reacted at 40° C. under nitrogen protection for 4 h to obtain a modified polyamic acid solution.

[0050] Step 3, preparation of engineering plastics: after mixing the hyperbranched polyamic acid solution obtained in the first step and the modified polyamic acid solution obtained in the second step in a mass ratio of 1:1, add 1 mol of acetic anhydride, stir and heat to 100°C, and dehydrate for 8 hours. After dehydration, cool, add water or ethanol, stir to precipitate, filter, take the precipitate, and dry to obtain impact-resistant and high-toughness polyimide. Example

[0051] Preparation of polyimide engineering plastics: The first step is to prepare a hyperbranched polyamic acid solution: KH550-modified titanium dioxide, 0.35-0.4 mol of pyromellitic dianhydride, 0.2 mol of 4,4′,4′′-triaminotriphenylmethane and N-methylpyrrolidone are mixed evenly to prepare a solution with a solid content of 25 wt%, and then reacted at 40° C. under nitrogen protection for 4 hours to obtain a hyperbranched polyamic acid solution, wherein the modified nano-titanium dioxide accounts for 25% of the total mass of the first dianhydride monomer and the triamine monomer, the particle size of the nano-titanium dioxide is 200-400 nm, and KH550 accounts for 12% of the mass of the nano-titanium dioxide in the KH550-modified nano-titanium dioxide.

[0052] Step 2: Preparation of modified polyamic acid solution: 0.1 mol of pyromellitic dianhydride, 0.1 mol of the branched diamine monomer prepared in Example 1 and N-methylpyrrolidone were uniformly mixed to prepare a solution with a solid content of 35 wt%, and then reacted at 0°C under nitrogen protection for 8 h to obtain a modified polyamic acid solution.

[0053] Step 3, preparation of engineering plastics: after mixing the hyperbranched polyamic acid solution obtained in the first step and the modified polyamic acid solution obtained in the second step in a mass ratio of 1:3, add 1 mol of acetic anhydride, stir and heat to 130°C, and keep warm for dehydration for 5 hours. After dehydration, cool, add water or ethanol, stir to precipitate, filter, take the precipitate, and dry to obtain impact-resistant and high-toughness polyimide.

[0054] Comparative Example 1 Preparation of polyimide engineering plastics: The first step is to prepare a hyperbranched polyamic acid solution: 0.35 mol of 4,4′-phthalic anhydride, 0.2 mol of 4,4′,4′′-triaminotriphenylmethane and N,N-methylformamide are mixed evenly to prepare a solution with a solid content of 15 wt%, and then reacted at 0°C under nitrogen protection for 8 hours to obtain a hyperbranched polyamic acid solution.

[0055] Step 2: Preparation of modified polyamic acid solution: Same as the second step in Example 3.

[0056] Step 3: Preparation of engineering plastics: Same as the third step in Example 3.

[0057] Comparative Example 2 Preparation of polyimide engineering plastics: The first step, preparation of hyperbranched polyamic acid solution: is the same as the first step in Example 3.

[0058] Step 2: Preparation of polyamic acid solution: 0.1 mol of 4,4′-phthalic anhydride, 2,2′-diphenylenediamine and N,N-methylformamide were uniformly mixed to prepare a solution with a solid content of 25 wt%, and then the reaction time was 8 hours at 0°C under nitrogen protection to obtain polyamic acid solution; Step 3: Preparation of engineering plastics: Same as the third step in Example 3.

[0059] Comparative Example 3 Preparation of polyimide engineering plastics: The first step, preparation of hyperbranched polyamic acid solution: the same as the first step in Comparative Example 1.

[0060] Step 2: Preparation of polyamic acid solution: same as the second step in Comparative Example 2; Step 3: Preparation of engineering plastics: Same as the third step in Example 3.

[0061] Comparative Example 4 Preparation of polyimide engineering plastics: Step 1: Preparation of modified polyamic acid solution: 0.1 mol of 4,4′-phthalic anhydride, 0.1 mol of the branched diamine monomer prepared in Example 1 and N,N-methylformamide were uniformly mixed to prepare a solution with a solid content of 25 wt%, and then reacted at 0° C. under nitrogen protection for 8 h to obtain modified polyamic acid solution.

[0062] Step 2: Preparation of engineering plastics: Add 0.5 mol of acetic anhydride to the modified polyamic acid solution, heat to 70°C with stirring, and dehydrate for 12 hours. After dehydration, cool, add water or ethanol, stir to precipitate, filter, take the precipitate, and dry to obtain polyimide.

[0063] Comparative Example 5 Preparation of polyimide engineering plastics: The first step is to prepare polyamic acid solution: 0.1 mol of 4,4′-phthalic anhydride, 2,2′-diphenylenediamine and N,N-methylformamide are mixed evenly to prepare a solution with a solid content of 25 wt%, and then reacted at 0°C under nitrogen protection for 8 hours to obtain polyamic acid solution.

[0064] Step 2: Preparation of engineering plastics: Add 0.4 mol of acetic anhydride to the polyamic acid solution, heat to 70°C with stirring, and dehydrate for 12 hours. After dehydration, cool, add water or ethanol, stir to precipitate, filter, take the precipitate, and dry to obtain polyimide.

[0065] The polyimides obtained in Examples 3-5 and Comparative Examples 1-5 were subjected to physical property tests, and the results are shown in Table 1. Among them, UV resistance test: the polyimide sample was placed in a xenon arc lamp box, and after accelerated aging with a xenon arc lamp for 1000 hours, the tensile strength of the test sample was taken out, and the tensile strength after accelerated aging with a xenon arc lamp was divided by the tensile strength before being placed in the xenon arc lamp box, that is, the tensile strength retention rate under UV resistance; Alkali resistance: the polyimide sample was immersed in an alkaline solution (sodium hydroxide solution with a mass concentration of 0.5%) and heated to 85°C in a water bath for 24 hours, then taken out, washed, dried, and the tensile strength of the sample after immersion was measured, and the tensile strength of the sample after immersion was divided by the tensile strength of the sample before immersion, that is, the tensile strength retention rate under alkali resistance.

[0066] Table 1 Tensile Strength Elongation at break Ultraviolet light resistance performance Tensile strength retention rate Alkali resistance performance Tensile strength retention rate unit MPa % % % Example 3 115 18.3 97.4 97.2 Example 4 128 17.5 97.6 97.7 Example 5 137 17.1 98.1 98.0 Comparative Example 1 96 19.6 75.6 97.2 Comparative Example 2 111 15.3 97.4 81.7 Comparative Example 3 106 14.1 75.3 81.6 Comparative Example 4 83 10.2 76.0 97.2 Comparative Example 5 81 7.8 98.4 98.4 From the data in Table 1, it can be seen that the polyimide obtained in Examples 3-5 has good tensile properties, UV resistance and alkali resistance.

[0067] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0068] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An alkaline hydrolysis-resistant polyimide engineering plastic, characterized in that: It is prepared by mixing a hyperbranched polyamic acid solution, a modified polyamic acid solution and a dehydrating agent and then undergoing a dehydration reaction; The hyperbranched polyamic acid solution is prepared by in-situ polymerization of modified nanoparticles, a first dianhydride monomer and a triamine monomer in a first solvent; The modified polyamic acid solution is prepared by polymerization reaction of a second dianhydride monomer and a branched diamine monomer in a second solvent; The branched diamine monomer is prepared by reacting aniline and benzaldehyde derivatives; The benzaldehyde derivative is prepared by reacting 4-hydroxybenzaldehyde and an epoxy silane coupling agent.

2. The alkaline hydrolysis-resistant polyimide engineering plastic according to claim 1, characterized in that: The mass ratio of the hyperbranched polyamic acid solution to the modified polyamic acid solution is 1:1-3; the solid content of the hyperbranched polyamic acid solution is 15-30wt%; and the solid content of the modified polyamic acid solution is 25-40wt%.

3. The alkaline hydrolysis-resistant polyimide engineering plastic according to claim 1, characterized in that: The dehydration reaction temperature is 70-130° C. and the reaction time is 5-12 hours.

4. The alkaline hydrolysis-resistant polyimide engineering plastic according to claim 1, characterized in that: The molar ratio of the first dianhydride monomer to the triamine monomer is 3.5-4:2; the reaction temperature in the in-situ polymerization reaction is 0-40°C, and the reaction time is 4-8h; the modified nanoparticles account for 15-35% of the total mass of the first dianhydride monomer and the triamine monomer.

5. The alkaline hydrolysis-resistant polyimide engineering plastic according to claim 1, characterized in that: The first dianhydride monomer is one of 4,4′-phthalic anhydride, 3,3′,4,4′-benzophenonetetracarboxylic dianhydride, pyromellitic acid dianhydride, and 4,4′-oxydiphthalic anhydride; the triamine monomer is 4,4′,4′′-triaminotriphenylmethane; and the first solvent is one or more of N,N-methylformamide, N,N-methylacetamide, and N-methylpyrrolidone.

6. The alkaline hydrolysis-resistant polyimide engineering plastic according to claim 1, characterized in that: The molar ratio of the second dianhydride monomer and the branched diamine monomer is 1:1; the reaction temperature in the polymerization reaction is 0-40°C, and the reaction time is 4-8h; the second dianhydride monomer is one of 4,4′-phthalic anhydride, 3,3′,4,4′-benzophenonetetracarboxylic dianhydride, pyromellitic dianhydride, and 4,4′-oxydiphthalic anhydride; the second solvent is one or more of N,N-methylformamide, N,N-methylacetamide, and N-methylpyrrolidone.

7. The alkaline hydrolysis-resistant polyimide engineering plastic according to claim 1, characterized in that: The branched diamine monomer is obtained by reacting aniline and benzaldehyde derivatives, comprising: After benzaldehyde derivative, aniline, aniline hydrochloride and dimethyl sulfoxide are uniformly mixed, reacted at 100-110°C for 1-3h under nitrogen protection, heated to 130-145°C, kept warm for 2-3h, the reaction is stopped, and post-processed to obtain a branched diamine monomer; The molar ratio of the benzaldehyde derivative to aniline is 1:2.5-3, and the added mass of the aniline hydrochloride is 3-6% of the mass of the benzaldehyde derivative and aniline.

8. The alkaline hydrolysis-resistant polyimide engineering plastic according to claim 1, characterized in that: The benzaldehyde derivative is prepared by reacting 4-hydroxybenzaldehyde with an epoxy silane coupling agent, comprising: After 4-hydroxybenzaldehyde, epoxysilane coupling agent and tetrahydrofuran are uniformly mixed, the pH of the system is adjusted to 10-11, heated to reflux under condensation, stirred and reacted for 2-4 hours, the reaction is stopped, and the benzaldehyde derivative is obtained through post-treatment; The molar ratio of the 4-hydroxybenzaldehyde to the epoxy silane coupling agent is 1:1-1.

3.

9. The alkaline hydrolysis-resistant polyimide engineering plastic according to claim 1, characterized in that: The dehydrating agent is acetic anhydride.

10. A method for preparing an alkali-hydrolysis-resistant polyimide engineering plastic according to any one of claims 1 to 9, characterized in that: include: The hyperbranched polyamic acid solution, the modified polyamic acid solution and the dehydrating agent are mixed, heated to a dehydration reaction temperature, and kept warm for dehydration. After the dehydration is completed, the polyimide with high impact toughness is obtained through post-treatment.

Citation Information

Patent Citations

  • Flexible hyperbranched semi-interpenetrating fluorinated polysiloxane polyimide film and preparation method thereof

    CN103113587A

  • Preparation method of high-transparency high-temperature-resistant fluorine-containing polyimide resin

    CN106496557A

  • Heat-resistant low-dielectric-constant polyimide film and preparation method thereof

    CN111748113A

  • High-brightness coating and preparation method thereof

    CN113736350A

  • Polyimide film with low linear expansion coefficient and preparation method thereof

    CN114106323A